COMPUTATIONAL CHEMICAL INVESTIGATION INTO ISORENIERATENE CYCLISATION - van Duin A.C.T.; Damste J.S.S. (My University, 2003)
In sediments, the diaromatic carotenoid isorenieratene can undergo a wide range of molecular transformations, including cyclisation reactions via a Diels-Alder mechanism resulting in either mono- and diaromatic compounds or tetracyclic isorenieratene derivatives. To study these complex diagenetic pathways, we have used molecular dynamics simulations, in concert with a newly developed reactive hydrocarbon force field (ReaxFF). This allows us to simulate the entire cyclisation pathway, including both stable intermediates as well as energy barriers related to transition states. Our simulations indicate that the formation of tetracyclic isorenieratene derivatives is likely to occur via an A-ring initiated reaction mechanism, as the reaction product resulting from A-ring closure is more stable than that derived from B-ring closure. Furthermore, the A-ring initiated tetracyclisation pathways contain one fewer high-energy hydrogen shift step than their B-ring initiated counterparts, indicating that B-ring initiated cyclisation is more likely to result in the formation of monoaromatic compounds. These observations are in excellent agreement with observed distributions of isorenieratene derivatives in sediments and provide a better understanding of the complex diagenetic pathways of isorenieratene.